Formulasi Legislative Drafting yang Ideal dalam Rangka Mewujudkan Negara Hukum yang Demokratis dan Menjunjung Nilai-Nilai Lingkungan - I Gusti Ayu Ketut Rachmi Handayani (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The formulations of ideal legislative drafting in the formation of environmental-based Regional Regulation is of highly essential matter to be done in a constitutional democracy. On this basis, the research problem in this research is how is the ideal formulation of legislative drafting in order to realize a democratic state of law, especially in the formation of environmental-based regional legal products? The method used in this research is a normative juridical method with qualitative analysis. As a result, this study highlights that in order to realize the ideal of a democratic state of law, the formulation of legislative drafting, especially in the formation of environmental-based regional legal products, should contain regionally-based materials of the specific condition of the area as well as further elaboration of higher legislation. The program establishment of regional regulation as instruments for program planning of Provincial Regulation or District / City Regulation arranged in a planned, integrated and systematic way, operationally lists the Regional Design Regulations which were organized based on certain method and parameters as an integral part of the national legislation system based on the Constitution of Indonesian Republic Year 1945 and the philosophy of the State.Formulation, legislative drafting, ideal, state of law, democratic.